DISASTER COMMUNICATION MANAGEMENT PUSDALOPS PB SLEMAN IN DISASTER INFORMATION COORDINATION - Tifani Octavia Leksono; Senja Yustitia; Christina Rochayanti (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2019)
The purpose of this study was to analyze disaster communication management activities carried out by the Sleman Emergency Operation Center in coordinating disaster information and identifying information coordination that occurred between Kab. Sleman, community, and non-governmental organizations @merapi_news. This study used descriptive qualitative method. Data search is done by in-depth interviews with parties involved in the disaster management process, namely Supervisors, Operators of PB Emergency Operations District. Sleman, the private organization @Merapi_news, and the Sleman community. The results of the study showed that the Sleman Emergency Operation Center was still not maximal in the implementation of the disaster communication management process. The lack of coordination of information that causes miss communication and distribution of disaster information to the community is often too late, the use of Instagram social media is not optimal by the Sleman Emergency Operation Center, and mitigation needs to be done simultaneously both BPBD and Pusdalops to shape the attitudes and knowledge of the community and implementing officers in disaster management.